Bargaining and Conflict with Up-Front Investments: How Power Asymmetries Matter - Zachary Schaller; Stergios Skaperdas (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine settings - such as litigation, labor relations, or arming and war - in which players first make non-contractible up-front investments to improve their bargaining position and gain advantage for possible future conflict. Bargaining is efficient ex post, but we show that a player may prefer Conflict ex ante if there are sufficient asymmetries in strength. There are two sources of this finding. First, up-front investments are more dissimilar between players under Conflict, and they are lower than under Bargaining when one player is much stronger than the other. Second, the probability of the stronger player winning in Conflict is higher than the share received under Nash bargaining. We thus provide a rationale for conflict to occur under complete information that does not depend on long-term commitment problems. Greater balance in institutional support for different sides is more likely to maintain peace and settlements.
Keywords: C70; D74; J53; K41; 330; power asymmetries; war; litigation; contests